2021
DOI: 10.3389/fendo.2021.670357
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Angiopoietin-Like 3 Levels in Healthy and Mild Preeclamptic Pregnant Women

Abstract: ObjectiveAngiopoietin-like protein 3(ANGPTL3) is an important regulator of lipoprotein metabolism in the fed state by inhibiting the enzyme lipoprotein lipase in oxidative tissues. However, the possible role of ANGPTL3 throughout gestation and its relationship with hormonal and biochemical variables are still unknown. The aim of this study was to determinate serum ANGPTL3 level in healthy non-pregnant women, during healthy and preeclamptic pregnancy and postpartum.MethodsSerum ANGPTL3 was analyzed by enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…In addition to the relation of ANGTPL3 with renal dysfunction, this hepatokine demonstrated a positive relationship with TG levels which is in line with previous findings. There are several lines of evidence that ANGPTL3 is associated with lipid profile and lipoprotein metabolism [ 29 , 30 ], ANGPTL3 indicated a positive association with TG in the Finnish population [ 31 ], patients with polycystic ovary syndrome [ 17 ] preeclamptic pregnant women [ 32 ]. Interestingly, ANGPTL3 showed a relation with proteinuria in patients with hyperlipidemia [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the relation of ANGTPL3 with renal dysfunction, this hepatokine demonstrated a positive relationship with TG levels which is in line with previous findings. There are several lines of evidence that ANGPTL3 is associated with lipid profile and lipoprotein metabolism [ 29 , 30 ], ANGPTL3 indicated a positive association with TG in the Finnish population [ 31 ], patients with polycystic ovary syndrome [ 17 ] preeclamptic pregnant women [ 32 ]. Interestingly, ANGPTL3 showed a relation with proteinuria in patients with hyperlipidemia [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Garces et al found that compared with healthy nonpregnant and postpartum women, serum ANGPTL3 levels were significantly lower in healthy pregnant women from the first trimester to the third trimester. It was speculated that serum ANGPTL3 may be involved in the changes of lipid metabolism in the anabolic and catabolic stages of pregnancy, which may help placental hormones become the main driving factor to regulate maternal lipid metabolism during pregnancy [ 53 ]. However, there was no significant difference in circulating concentrations of ANGPTL4 [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes are essential for fetal growth and delivery. However, the situation is complicated by the pre-eclampsia [14][15][16]. Several studies have already summarized the clinical characteristics of the general pre-eclampsia population [17,18].…”
Section: Introductionmentioning
confidence: 99%